Relationship analysis based on phytochemical contents among coffee pulp from three coffee species collected in Southern Thailand and Jambi, Indonesia - YUDITHIA MAXISELLY; HARIS MAULANA; AMORNRAT CHUMTHONG; RAWEE CHIARAWIPA (Society for Indonesian Biodiversity, 2023)
Abstract. Maxiselly Y, Maulana H, Chumthong A, Chiarawipa R. 2023. Relationship analysis based on phytochemical contents among coffee pulp from three coffee species collected in Southern Thailand and Jambi, Indonesia. Biodiversitas 24: 5439-5445. Coffee pulp is part of the coffee cherry, except for the seed, and has many benefits for human health. The research aimed to analyze phytochemical contents and the relationship among the coffee pulp of three coffee species: Coffea arabica (Arabica), Coffea canephora (Robusta), and Coffea liberica (Liberica), collected in southern Thailand and Jambi, Indonesia. The coffee pulp of Arabica from Indonesia dominated in three variables: antioxidant activity (67.37±11.83 mg/100g DW), tannin (40.71 ±3.52 mg/100g DW), and phenolic (50.47±5.43 mg/100g DW). Robusta coffee pulp from Thailand contained a lower value of all phytochemical components. However, the coffee pulp of Liberica from Thailand had the highest value for flavonoid content (18.19±0.95 mg/100g DW) and saponin content (0.77±0.09 g/100g DW) among the three species in both countries. Principal Component Analysis (PCA) also supports the result, which shows connectivity among antioxidant activity, tannin, and phenolic to Arabica from Indonesia, with flavonoid and saponin to Liberica from Thailand. These results indicate both the species and the environment influenced the phytochemical compositions of coffee pulp. Thus, Indonesia may benefit from developing more Arabica and Robusta coffee pulp products, while Thailand may benefit from creating the Liberica coffee pulp product.